APA Educational Psychology Handbook, Vol 1: Theories, Constructs, and Critical Issues. 2012
DOI: 10.1037/13273-015
|View full text |Cite
|
Sign up to set email alerts
|

Self-concept: A synergy of theory, method, and application.

Abstract: There is a revolution sweeping psychology, one that emphasizes a positive psychology and focuses on how healthy, normal, and exceptional individuals can get the most from life (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(65 citation statements)
references
References 94 publications
2
55
0
8
Order By: Relevance
“…In the relatively few cross-cultural studies published in major personality journals, the focus has typically been on cross-cultural differences rather than cross-cultural generalizability (Chiu et al, 2008;Chiu, 2012). Marsh, Xu, and Martin (2012;Segall, Lonner, & Berry, 1998;Van de Vijver & Leung, 2000) emphasized that in crosscultural research, there are two main contrasting perspectives. Cultural relativist (idiographic, emic, and qualitative) perspectives accentuate the individual's uniqueness that undermines comparison.…”
Section: Cross-cultural Generalizability Of Psychological Comparisonmentioning
confidence: 99%
“…In the relatively few cross-cultural studies published in major personality journals, the focus has typically been on cross-cultural differences rather than cross-cultural generalizability (Chiu et al, 2008;Chiu, 2012). Marsh, Xu, and Martin (2012;Segall, Lonner, & Berry, 1998;Van de Vijver & Leung, 2000) emphasized that in crosscultural research, there are two main contrasting perspectives. Cultural relativist (idiographic, emic, and qualitative) perspectives accentuate the individual's uniqueness that undermines comparison.…”
Section: Cross-cultural Generalizability Of Psychological Comparisonmentioning
confidence: 99%
“…Porém, segundo Marsh, Xu e Martin (2012), ambos os construtos têm provado serem multidimensionais, contendo tanto aspectos globais quanto domínios específicos, sendo essa distinção insustentável. Em concordância com Marsh et al (2012) e Trautwein e Möller (2016), no presente estudo ambos os construtos foram propostos e identificados no nível específico referente às habilidades escolares, exemplificando que tanto o autoconceito quanto a autoeficácia podem ser mensurados no nível mais específico do domínio ligado à tarefa.…”
Section: Discussionunclassified
“…O outro ponto de distinção entre autoconceito e autoeficácia apresentado na literatura diz respeito ao efeito do quadro de referência (Bong & Skaalvik, 2003;Byrne, 1996;Marsh et al, 2012;Neves & Faria, 2009). É defendido que respostas a itens de autoconceito tenderiam a ser mais influenciadas por comparações sociais com os pares (referencial externo), ou por comparações de sua própria habilidade em outras tarefas (referencial interno).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In meta-analyses, effect sizes ranging from 0.32 to 0.41 are reported (Hattie, 2009(Hattie, , 2012. Research based on longitudinal assessment and structural equation modeling of both self-concept and achievement has demonstrated that self-concept depends on former achievement (skill-development model) but also predicts subsequent achievement (self-enhancement model) (Helmke and van Aken, 1995;Marsh et al, 2012). Correlations are especially high, when self-concept is conceptualized as domain-specific, and when pupils are older (Helmke and Weinert, 1997).…”
Section: Self-conceptmentioning
confidence: 99%